Building memristive and radiation hardness TiO2-based junctions - Ghenzi, Néstor (2013)
We study micro-scale TiO2 junctions that are suitable to be used as resistive random-access memory nonvolatile devices with radiation hardness memristive properties. The fabrication and structural and electrical characterization of the junctions are presented. We obtained a retentivity of 105 s, an endurance of 104 cycles and reliable switching with short electrical pulses (time-width below 10 ns). Additionally, the devices were exposed to 25 MeV oxygen ions. Then, we performed electrical measurements comparing pristine and irradiated devices in order to check the feasibility of using these junctions as memory elements with memristive and radiation hardness properties.